Tantangan Etika Dalam Profesi Teknologi Informasi - Zebua, Della Yunika; Zebua, Alfan Pintalius (CV. SINAR HOWUHOWU, 2025)
The profession in Information Technology (IT) poses many challenges, especially related to ethics, especially in privacy and data security. In working, IT professionals must face ethical dilemmas. They must balance between using innovative technology and protecting users' personal information. Professional ethics in IT are rules that determine how a professional should act, including maintaining integrity and honesty. This is important to maintain public trust in the technology services provided. However, with the increasing number of digital activities and data usage, the risk of data misuse and privacy violations is also increasing. In addition, the use of the internet as a modern communication tool also raises concerns about increasing privacy violations. This study focuses on the study of ethical principles in IT work and the issues that arise in data protection and privacy in the digital age. By understanding ethical rules and regulations on privacy, hopefully awareness of ethics will increase and data security practices can be improved to reduce the risk of privacy violations.